Joint demonstration by Tanzanians and South African exiles in Dar-es-Salaam in support of the liberation struggle in South(ern) Africa
Joint demonstration by Tanzanians and South African exiles in Dar-es-Salaam in support of the liberation struggle in South(ern) Africa.